Efficacy of Bacillus clausii UBBC-07 in the prevention of antibiotic-associated diarrhea in children - H.V. Beketova; O.O. Koiro; S.S. Bohdanova; M.S. Bulhakova; K.M. Heorhitsa; O.B. Il’kiv; О.R. Kavka; О.Z. Kmit’; О.V. Kukhar; V.І. Liubetska; V.V. Maleiko; І.А. Matiukhina; et al. (Zdorovʹe Rebenka)
The effectiveness of the probiotic strain Bacillus clausii UBBC-07, was evaluated in the prevention of antibiotic-associated diarrhea. The study analyzed the treatment outcomes of 939 patients aged 28 days to 18 years with bacterial infections of various localizations, receiving systemic antibacterial therapy. Patients who took Bacillus clausii UBBC-07 simultaneously with antibiotics (n = 671) were assigned to the treatment group, while those who did not receive the probiotic on the background of antibiotic therapy (n = 268) were included in the control group. The treatment outcomes were evaluated in 794 patients (565 from the treatment group and 229 controls), for whom the prescribed antibacterial agent was known. In the treatment group, there was a significantly lower incidence of gastrointestinal disturbances compared to the control group, specifically diarrhea (5.5 vs. 14.0 %) and abdominal pain (3.7 vs. 7.4 %). Prophylactic use of the probiotic reduced the frequency of developing antibiotic-associated diarrhea in general by 2.5 times, with a reduction of 2.5 times among patients receiving penicillins, of 2.4 times among those treated with cephalosporins, and of 5.1 times for those who took macrolides. Bacillus clausii UBBC-07 also decreased the duration of loose stools in patients with diarrhea (1.84 days in the treatment group vs. 2.66 days in the control one) and the average number of days with abdominal pain in those who reported discomfort (1.25 vs. 1.71 days, respectively). Thus, the use of Bacillus clausii UBBC-07 from the first day of antibacterial therapy in children contributes to the effective prevention of antibiotic-associated diarrhea, significantly improving patients’ quality of life, accelerating their recovery, and reducing the likelihood of complications.